THE IMPORTANCE OF EARLY DIAGNOSIS AND TREATMENT OF SARCOPENIA IN THE PREVENTION OF FALLS IN THE ELDERLY - Filip Maciej Huzarski,; Katarzyna Dziepak,; Katarzyna Adrianna Tryniecka,; Katarzyna Maria Turek,; Weronika Worosz,; Alicja Zań,; Diana Zofia Wisz, (International Journal of Innovative Technologies in Social Science, 2025)
Objective: The aim of this study was to identify early diagnostic methods and determine their importance, as well as to establish effective treatment methods for sarcopenia in preventing falls in older adults.Materials: A detailed literature review was conducted using the Scholar and PubMed databases for peer-reviewed articles published between 2020 and 2025. Systematic reviews, meta-analyses, and relevant clinical guidelines were included.Conclusions: Sarcopenia is a significant, yet modifiable, risk factor for falls in older adults. Early diagnosis and symptom detection, combined with multifaceted therapeutic interventions can significantly reduce the number of falls, improve quality of life, and reduce healthcare costs.